Clinical outcome of deep infiltrating colorectal endometriosis surgeries in the Endometriosis Center of the University of Gießen and Marburg between 2005-2015 - Berkes, Enikö; Justus Liebig University Giessen (My University, 2021)
The gold standard of treatment for colorectal endometriosis is the surgical removal of the lesion with shaving, disc excision or segmental colorectal resection. Which method is the most appropriate is controversial and clear criteria for the choice of surgery are missing. We conducted a retrospective cohort study of 120 patients, who underwent colorectal endometriosis surgery at the Endometriosis Center of the University of Gießen and Marburg between 2005 and 2015 in order to define clear criteria for each surgical modality and assess clinical outcome. We analysed the clinical records of the patients and answers of a self-developed questionnaire as well as telephone interviews. 75 patients underwent segmental colorectal resection, 19 disc excision and 26 shaving. The mean age of the patients was 34 years. 78% of the patients suffered from pain symptoms and 58% had a pregnancy wish. The surgery lasted an average of 292 minutes with a mean hospital stay of 5, 6 and 7 days after shaving, disc excision and segmental resection, respectively. The bowel lesion was associated in every second patient with endometriosis of the ovaries and in every third patient with infiltration of the vagina, rectovaginal space, sacrouterine ligaments and pelvic side walls. The majority of the bowel lesions in the shaving procedures measured up to 3cm and infiltrated the serosa and subserosa. With disc excision mainly lesions between 3-6cm with muscularis layer infiltration were removed. In the segmental resection group every third patient had multifocal, long segment affection of the bowel wall and 10% multicenter lesions with 2-3 nodules. The lesions infiltrated at least the muscularis and in 25% and 7% the submucosa and mucosa, respectively. All procedures improved significantly the pain symptoms, bowel dysfunctions and libido as well as the reproductive results. The pregnancy and delivery rates revealed 57% and 39%, respectively. Two patients underwent a severe labour complication with rupture of the posterior uterine and vaginal vault. We observed a histological recurrence of endometriosis in 9% of the patients, having one patient both in the disc excision and shaving group with recurrence of bowel endometriosis. Recurrence of bowel endometriosis did not occur after segmental resection. The segmental resection was associated with the highest intra- and postoperative complication rates having an injury of the ureter and anastomotic leakage. We can conclude that none of the procedures are superior to the other one regarding clinical outcome. Small superficial lesions should be removed with shaving. Singular nodules with muscular infiltration are appropriate for disc excision. Lesions with multifocal or multicentre character, or isolated nodules with infiltration up to the mucosa and significant bowel circumference involvement should be treated with segmental colorectal resection.
Keywords: deep infiltrating endometriosis; bowel endometriosis; surgery; ddc:610